Aerospace structures and engines from polymer composites - Mat Yazik M.H.; Ismail I. (Elsevier, 2025)
The application of polymer composites in aerospace has transformed aircraft design and performance. Lightweight wings and control surfaces benefit from these composites, offering remarkable strength-to-weight ratios, enhancing maneuverability, and improving fuel efficiency. Notable examples include the Boeing 787 Dreamliner?s composite wings and the Airbus A350 XWB?s carbon fiber-reinforced plastic control surfaces. Additionally, polymer composites have found their place in aircraft fuselage structures. Composite materials are instrumental in the construction of fan blade and casing, offering lightweight solution, and promoting thermal resistance in combustion chambers. Exhaust nozzles and thrust reversers benefit from polyimides and bismaleimides, ensuring stability and weight reduction. These advancements highlight the profound impact of polymer composites on aviation, with future research directions including sustainability, multifunctional composites, nanotechnology integration, and further innovations in safety and performance. ? 2025 Elsevier Inc. All rights reserved.